Eco-innovation of enterprises operating in Poland against the background of European Union countries - D. Wielgórka; W. Szczepaniak (Global Journal of Environmental Science and Management)
Eco-innovation is any innovation that leads to sustainable development by limiting the negative impact of production activities on the environment, increasing the resilience of nature to loads or ensuring greater efficiency and responsibility in the use of natural resources. Eco-innovations are the opportunity for enterprises. Their introduction contributes to reducing the costs of doing business, allows you to take advantage of new opportunities development and positively affects the company's image. The main goal of the research is to recognize the situation and the level of eco-innovation in Poland, including the micro, small and medium enterprises sector and to compare the obtained results with the ones from European Union countries. The result of the research is indicating the barriers and opportunities to support the development of eco-innovation in the micro, small and medium enterprises sector in Poland. Lack of financial resources for eco-innovation was indicated as the largest barrier by MSMEs in Poland. The most significant barriers to eco-innovation in Poland are mainly of an economic nature, including the high cost of implementation, difficult access to capital, uncertain return on investment and the weak system of economic and fiscal incentives encouraging eco-innovation.